Significance of urine albumin / creatinine ratio (UACR) and uric acid in women with preeclampsia and its comparison with healthy normotensive pregnant women in their third trimester - Sogani, Sonal; Varma, Vandana; Sarkar, Purnima Dey (Acta medica Lituanica, 2014)
Objective. To determine the significance of urine albumin / creatinine ratio (UACR) as to predict proteinuria in new-onset hypertension and uric acid in women with preeclampsia and its comparison with healthy normotensive pregnant women. Methods. Healthy normotensive pregnant women (n = 45), women with preeclampsia (n = 36) were included in the study. The preeclamptic group was further divided into two subgroups: mild (n  =  25) and severe preeclampsia (n = 11). Results. Higher mean values of urine albumin / creatinine ratio (UACR) and uric acid were found in preeclamptic pregnant women (319.05 ± 247.56 mg/g, 5.98  ±  2.1  mg/dl) as compared to healthy normotensive pregnant women (22.15  ±  8.1  mg/g, 4.07  ±  0.91  mg/dl) in the third trimester with highly significant difference (p
Keywords: preeclampsia; urine albumin / creatinine ratio (UACR); uric acid; proteinuria